IMPLEMENTASI STANDAR PENDIDIK DAN TENAGA KEPENDIDIKAN PADA SEKOLAH DASAR: STUDI KOMPARATIF DI SDN 4 PENEBEL DAN SDN 1 BIAUNG - Ayu Ketut Wiraswaryani; I Gede Made Ari Arta Nugraha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The standard of educators and education personnel is a main pillar in ensuring the quality of basic education. This study aims to analyze and compare the implementation of educator and education personnel standards at SDN 4 Penebel and SDN 1 Biaung, which are situated in semi-rural and rural areas of Penebel District, Tabanan Regency, Bali Province. The research method employed is descriptive qualitative with a comparative study approach. Data were collected through observation, in-depth interviews, and documentation studies. The results indicate that normatively both schools have met the minimum academic qualifications (S1/D4) and all teachers possess educator certificates, fulfilling the requirements of Permendiknas No. 16 of 2007 and Government Regulation No. 57 of 2021. Substantively, teachers in both schools demonstrate adaptive pedagogical and professional competencies, particularly in integrating digital devices such as Interactive Flat Panel (IFP) and Chromebooks into the learning process based on the Merdeka Curriculum. The novelty of this study demonstrates that the quality of teachers' digital competence is not inherently dictated by the school's geographical location, but is more significantly driven by human resource readiness (human capital) and internal school support. However, structural challenges in the form of the absence of a definitive principal at one school, alongside the lack of computer laboratory facilities and specialized library personnel, remain systemic barriers to optimizing quality assurance in both institutions. This study recommends that the Tabanan District Education Office immediately intervene with structural policies to address these gaps.